The ASSOCIATION BETWEEN MICROTRANSACTION IN VIDEO GAMES WITH VIDEO GAME ADDICTION AMONG PRECLINICAL MEDICAL STUDENTS IN ATMA JAYA CATHOIC UNIVERSITY OF INDONESIA FACULTY OF MEDICINE AND HEALTH SCIENCE - Reinardus Alexander Ricky (Atma Jaya Catholic University of Indonesia, 2021)
ABSTRACT Introduction: Video game addiction is a control impairment over the desire to play video games that stems from a habbit of prolonged gaming with high intensity. One of its causes are in-game microtransactions. Microtransaction involves various purchases within a video game by using real-life money. Microtransactions can make games easier, customize in-game looks, and earn rare in-game items. This is suspected to increase gaming intensity and duration. This research aims to find out the association between microtransaction in video games and video game addiction among medical students in Atma Jaya Catholic University of Indonesia. Methods: This study is an observational-analytical study with a cross-sectional approach with a total of 70 respondents. The respondents consist of medical students from class years 2016-2018 at Atma Jaya Catholic University that fulfil the inclusion and exclusion criterias. The data was collected by distributing an online survey to each PBL groups from each class years. Questionnaires used are Video Game Addiction Test (VAT) to assess video game addiction and microtransaction questionnaire to assess in-game microtransactions. Data analysis was done using a computer program. Results: The number of male and female respondents are equal. This study has found 32.9% of students with video game addiction. The proportion of students who have carried out in-game microtransactions is 41.4%. Chi square test shows that there is a significant association between in-game microtransactions and video game addiction (p = 0.001), with an odds ratio of 6. Conclusion: There is a significant association between microtransaction in video games with video game addiction. Keywords: microtransaction in video games, pre-clinical medical student, video game addiction